Attitudes towards FCTC Article 5.3 among tobacco control stakeholders in Thailand and their relationship with awareness of tobacco industry tactics - Roengrudee Patanavanich; Paweena Punkrajang; Jaruayporn Ingkasereepitak; Warodom Phaenthong; Chantapol Yimnual; Sarin Katithamanit; Praepilai Wichakpan (BMJ Global Health)
Background Article 5.3 of the WHO Framework Convention on Tobacco Control (FCTC) was developed to protect public health policies from tobacco industry interference. The guiding principles of Article 5.3 emphasise a fundamental conflict between the tobacco industry’s interests and public health interests (principle 1) and recommend that the government be accountable and transparent (principle 2), demand accountability and transparency from the industry (principle 3), and refrain from providing incentives to the industry (principle 4). This study quantitatively explored attitudes towards Article 5.3’s guiding principles and recommendations among Thai tobacco control stakeholders and whether they were associated with awareness of tobacco industry tactics.Methods We conducted an online survey of 703 individuals involved in tobacco control in Thailand . We employed multivariable ordinal logistic regression analysis to explore factors associated with attitudes towards Article 5.3’s guiding principles and recommendations.Results 441 participants responded to the survey (response rate 62.7%). Among the Article 5.3 guiding principles, principle 1 received the lowest agreement (83%), whereas the other three principles had an average of 93% agreement. In multivariable ordinal logistic regression, we found awareness of tobacco industry tactics was associated with Article 5.3’s guiding principles: principle 1 (adjusted OR (AOR) 1.11; 95% CI 1.07 to 1.15; p<0.001), principle 2 (AOR 1.07; 95% CI 1.02 to 1.12; p=0.002), principle 3 (AOR 1.11; 95% CI 1.06 to 1.15; p<0.001) and principle 4 (AOR 1.14; 95% CI 1.09 to 1.19; p<0.001). In addition to awareness of tobacco industry tactics, age, years of experience in tobacco control, role in tobacco control and smoking by family members and friends were associated with perspectives towards Article 5.3’s guidelines.Conclusions This study provides quantitative evidence of the association between attitudes towards WHO FCTC Article 5.3 and awareness of tobacco industry tactics in Thailand. Denormalisation of the tobacco industry is thus a vital component of successfully implementing and enforcing Article 5.3.